Evaluating the Toxicity and Histological Effects of Al2O3 Nanoparticles on Bone Tissue in Animal Model: A Case-Control Study - Hossein Soltaninejad; Hadi Zare-Zardini; Amir Ali Hamidieh; Mohammad Reza Sobhan; Seyed Houssein Saeed-Banadaky; Mohammad Amir Amirkhani; Behnaz Tolueinia; Mohsen Mehregan; Mahnaz Mirakhor; Farzaneh sadat Eshaghi (Journal of Toxicology)
The applications of nanostructures have been limited by their different toxicities. So, the investigation of these toxicities is necessary before nanostructure application. This study aimed to evaluate the effect of aluminum oxide (Al2O3) nanoparticles on bone density in Wistar rat. Al2O3 nanoparticle was prepared by the sol-gel method. Characterization was done by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Sixty-four male adult Wistar rats were divided into eight groups including six groups intravenously treated with Al2O3 nanoparticle at concentrations of 25, 50, 100, 250, 500, and 1000 µg/ml: one group received food and water as the control group, and one group received food and water as well as intravenously distilled water as an injection control group. After 41 days, bone density was analyzed by dual-energy X-ray absorptiometry (DEXA). According to X-ray diffraction, the average particle size for Al2O3 nanoparticles was 20.85 nm. The data of densitometry showed that the bone density of right and left foot was reduced in concentrations of 250, 500, and 1000 µg/ml that were statistically significant in comparison with the control group. The reduction of bone density was increased with the enhancement of nanostructures concentration. The effect of Al2O3 nanoparticles on bone density was similar in the left and right legs. Histopatholological assessment also showed that Al2O3 nanoparticles (250, 500, and 1000 µg/ml) lead to significant reduction of trabeculae. Empty lacunae are observed in these three groups. Considering that high concentrations of Al2O3 nanoparticles had toxicity on bone tissue, it must be used by more caution, especially its use as a coating in different devices such as implants, surgical instruments, and bone prostheses.